1990
DOI: 10.1113/expphysiol.1990.sp003424
|View full text |Cite
|
Sign up to set email alerts
|

5‐Hydroxytryptamine mediates the post‐embolic increase in respiratory rate in anaesthetized rabbits

Abstract: SUMMARYThe effect of the neuronal 5-HT3 receptor antagonist MDL 72222 has been investigated on the reflex tachypnoeic response to pulmonary embolism in pentobarbitone-anaesthetized rabbits.Pre-treatment with MDL 72222 (640 ,tg kg-1, 5 min prior to embolization) significantly attenuated the reflex tachypnoeic response associated with the injection of emboli. MDL 72222 had no effect on the bradycardia associated with embolization; however, it significantly reduced the decrease in arterial blood pressure and conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Following systemic allergen or endotoxin exposure, platelets accumulate in the lungs of mice and release serotonin which is thought to contribute to the pathophysiology of anaphylactic shock (Yoshida et al 2002). Experimental pulmonary embolism in rabbits leads to serotonin release (presumably from platelets) that in turn stimulates 5-HT3 receptors on intrapulmonary vagal C-fibres causing reflex tachypnoea (Armstrong & Kay, 1990). Intrapulmonary entrapment of activated platelets leads to reflex-mediated circulatory collapse in part due to 5-HT3 receptor-mediated afferent nerve activation (Kay & Armstrong, 1991).…”
Section: Role Of Endogenous Serotoninmentioning
confidence: 99%
“…Following systemic allergen or endotoxin exposure, platelets accumulate in the lungs of mice and release serotonin which is thought to contribute to the pathophysiology of anaphylactic shock (Yoshida et al 2002). Experimental pulmonary embolism in rabbits leads to serotonin release (presumably from platelets) that in turn stimulates 5-HT3 receptors on intrapulmonary vagal C-fibres causing reflex tachypnoea (Armstrong & Kay, 1990). Intrapulmonary entrapment of activated platelets leads to reflex-mediated circulatory collapse in part due to 5-HT3 receptor-mediated afferent nerve activation (Kay & Armstrong, 1991).…”
Section: Role Of Endogenous Serotoninmentioning
confidence: 99%
“…Although not specifically identified as the mediator(s) involved in this electrophysiological study (3), many mediators such as cyclooxygenase metabolites, oxygen radicals, histamine, and serotonin could be released as a consequence of platelet aggregation (18). In their studies, Armstrong and co-workers (1,4) showed that the reflex tachypneic response to glass-bead microembolization in rabbits was totally prevented by platelet depletion and partially attenuated by pretreatment with a serotoninreceptor antagonist. The tachypneic response to microembolization in rabbits has been shown to be a reflex elicited by the stimulation of pulmonary C fibers (12).…”
mentioning
confidence: 97%
“…These results suggest that 1) cyclooxygenase products are necessary for the stimulation of PCs by PAE, whereas changes in lung mechanics are not, and 2) the functional importance of cyclooxygenase products may be mediated in part through the formation of z OH. lung vagal sensory receptors; microembolism; reflex tachypnea; ibuprofen; dimethylthiourea; cyclooxygenase system; hydroxyl radical PULMONARY MICROEMBOLISM is known to cause reflex tachypnea (1,4,12). Vagal lung C-fiber afferents are believed to play an important role in eliciting this respiratory response (1,4,12).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15,28 The brain regions with a high density of 5-HT3 receptors are the area postrema, olfactory bulb and amygdala. 29 Ondansetron is a drug that is well absorbed from the gastrointestinal tract and rapidly penetrates the brain barriers.…”
Section: Discussionmentioning
confidence: 99%